2017
DOI: 10.1089/nat.2016.0634
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Microsurgery Using Aptamer-Functionalized Magnetic Microdisks for Tumor Cell Eradication

Abstract: Magnetomechanical cell disruption using nano- and microsized structures is a promising biomedical technology used for noninvasive elimination of diseased cells. It applies alternating magnetic field (AMF) for ferromagnetic microdisks making them oscillate and causing cell membrane disruption with cell death followed by apoptosis. In this study, we functionalized the magnetic microdisks with cell-binding DNA aptamers and guided the microdisks to recognize cancerous cells in a mouse tumor in vivo. Only 10 min of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Although without statistical validation, we can observe some trends based on all the in vitro studies. As shown in Table 2 (column 6), apoptosis represents, in most cases, the latest stage of the above cited cellular perturbations, 21,22,25,27,30,32,[36][37][38][39][40][41][42][43]46,[50][51][52] however with variable rates of cancer cells mortality (or viability). Some of the studies show the induction of necrosis onlysuch as necrotic membrane disruption, cell membrane leakage or cell lysis.…”
Section: Comments On the In Vitro Apoptotic Occurrence In Tmmepmentioning
confidence: 99%
See 1 more Smart Citation
“…Although without statistical validation, we can observe some trends based on all the in vitro studies. As shown in Table 2 (column 6), apoptosis represents, in most cases, the latest stage of the above cited cellular perturbations, 21,22,25,27,30,32,[36][37][38][39][40][41][42][43]46,[50][51][52] however with variable rates of cancer cells mortality (or viability). Some of the studies show the induction of necrosis onlysuch as necrotic membrane disruption, cell membrane leakage or cell lysis.…”
Section: Comments On the In Vitro Apoptotic Occurrence In Tmmepmentioning
confidence: 99%
“…The effect was maximal at the highest frequency (20 Hz) as well as the highest eld strength (20 mT). 50 In vivo tests were also performed by Zamay et al 40 by injecting adenocarcinoma cells into the mouse thigh. One hour aer intra-tumor injection of the particles (nickel nanodiscs), mice were subjected to a eld of 100 Oe (i.e.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…1). LC-17 and LC-18 possess high affinity to post operative lung tissue with kd= 14 nM, and 38 nM correspondingly [10], bound different ligands and were already successfully applied as reporter for characterization of histological structure of lung adenocarcinoma [11]. To test the approach, model solid-phase microassay of sandwich type was carried out using the samples of postoperative cancer and healthy lung tissues as targets (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All of them demonstrated high affinity to the tumor tissue elements (mostly cells) and the binding absence with healthy lung tissue and blood cells. Fluorescently labeled aptamers from this group -LС-17 and LC-18, were successfully applied for detection of blood circulating tumor cells in patients with lung adenocarcinoma by confocal fluorescent microscopy [10] and for histological examinations of lung adenocarcinoma [11]. The aim of our research was to develop the solid-phase assay based on this couple of aptamers (LС-17 and LC-18) as sensing elements and the recombinant Ca 2+ -regulated photoprotein obelin as a high sensitive bioluminescent reporter to detect lung tumor elements circulating in blood.…”
Section: Introductionmentioning
confidence: 99%
“…and Zamay T.N. [ 116 , 118 ], the antitumor effect of DNA aptamer modified nickel magnetic microdisks coated with gold, was investigated in vivo and in vitro. It was found that the DNA aptamer modified microdisks, under the influence of a rotating magnetic field, are capable of causing death of ascites cells, in cell culture or in an organism [ 116 , 118 ] ( Figure 7 ).…”
Section: Application In Therapymentioning
confidence: 99%